Within‐couple dissimilarities in functional impairment as determinants of spousal care arrangement among older married couples. Issue 2 (2nd March 2021) - Liu, Huiying; Li, Yuekang; Wang, Yi; Morrow‐Howell, Nancy; Lou, Vivian W. Q.; Shen, Huei‐Wern
Abstract: Existing research on spousal care focuses on one spouse receiving care from the other, which fails to address the complexity that is created when both spouses experience some impairments. Our study included situations in which one or both spouses have functional impairments when examining the extent to which spouses from the same couple hold a (dis)similar level of functional impairment and whether such within‐couple (dis)similarity has an impact on the spousal care arrangement. A subsample of 1170 older married couples was selected from the 2014 Health and Retirement Study. Descriptive statistics were used for describing the level of each spouse's functional impairment regarding the number of limitations in activities (activities of daily living [ADL]) or instrumental ADL (IADL). Logistic regressions were used to examine whether spousal dissimilarity in functional impairment (dissimilar, similarly low, similarly high) was associated with spousal care arrangement. Within couples with one functionally impaired spouse, the impaired spouse was more likely to receive spousal care when reporting a higher level of ADL/IADL impairment. Within couples with two functionally impaired spouses, the more impaired person was more likely to receive spousal care (without giving back) when spouses reported dissimilar level of IADL impairment; spouses were more likely to report mutual care when they had similarly high levels of IADL impairment. By documenting the role of spousal dissimilarities in functioning for determining spousal care arrangement, our study can inform couple‐based interventions that capitalize on each spouse's capabilities and resources.